Analisis Perencanaan Bahan Baku Dalam Peningkatan Efisiensi Produksi Pada UMKM Cookies & Desseart By Me - Aulia, Sarah Elvina; S, Sungkono (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The most significant growth is the food industry. Many business actors have started operating in the culinary industry with various types of businesses, such as cafes, bakeries and bakeries, and food businesses that are almost complete. One of the micro businesses operating in the culinary sector is Cookies & Dessart by me, which produces cookies and desserts. Consumers can be satisfied and maintain competition with good management in an efficient and maximal production process. This research uses quantitative analysis. This research is used to study a subject as a whole about how to plan raw material supplies effectively to increase production efficiency at Desseart & Cookies By Me MSMEs. Forecasting (forecasting) methods and Raw Material Requirements are used. According to the information collected, the efficiency level of raw material supplies has not reached the expected efficiency level, which is indicated by the average efficiency level of 16.13111.